RE: Could Hepatitis B Reactivation Be Overlooked in Patients with Resolved HBV Infection and Receiving Immunosuppressive Treatment? - Han, Pingyang; Wang, Ziqiu; Wang, Zhaohui (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Han P, Wang Z, Wang Z. RE: Could hepatitis B reactivation be overlooked in patients with resolved HBV infection and receiving immunosuppressive treatment? Turk J Gastroenterol. 2024;35(4):352-353.